The Effect of Casein Phosphopeptide-amorphous Calcium Fluoride Phosphate on the Remineralization of Artificial Caries Lesions: An In Vitro Study - Nhu, Ngoc Ngoc Vo Truong; Hong, Thuy Pham Thi; Quynh, Anh Le; Minh, Son Tong; Thu, Nguyen Thi (Journal of Dentistry Indonesia, 2017)
The studies on electron microstructure of the effect of the use of products that contain casein phosphopeptide-amorphous calcium fluoride phosphate (CPP-ACPF) on enamel remineralization are still needed. It is important method to observe of the morphological changes of teeth in different conditions. Objective: To evaluate the remineralization potential of paste on enamel lesions using scanning electron microscopy (SEM). Methods: Sixty enamel specimens were prepared from extracted human premolars. The specimens were placed in a demineralizing solution for four days to produce artificial carious lesions. The specimens were then randomly assigned to two study groups: group A (control group) and group B. Group B was incubated in remineralizing paste (CPP-ACPF) for 30 minutes per day for 10 days. The control group received no intervention with remineralizing paste. All 60 specimens were stored in artificial saliva at 370C. After remineralization, the samples were observed using SEM. Results: The statistical analysis showed a decrease in the lesion area between the demineralized and remineralized samples, but no significant difference was observed in the lesion depth for group B. There was a significant increase observed in both the lesion depth and lesion area for group A (p = 0.03). Conclusion: The results showed the capacity of CPP-ACPF in supplying calcium and phosphate to the enamel, decreasing the dissolution of the enamel surface and increasing the remineralization of the enamel surface.